Influence of complications following immediate breast reconstruction on breast cancer recurrence rates. Issue 4 (18th February 2016) - Beecher, S M; O'Leary, D P; McLaughlin, R; Sweeney, K J; Kerin, M J
Abstract: Background: The rate of immediate breast reconstruction is rising. Postoperative infections are more frequent in patients who undergo reconstruction. The inflammatory response to a postoperative infection can increase the risk of tumour recurrence in other forms of cancer through the release of proinflammatory mediators. The aim of this study was to assess the relationship between complications and breast cancer recurrence in patients undergoing immediate reconstruction. Methods: This was a review of a prospectively maintained database of all patients who had immediate breast reconstruction between 2004 and 2009 at Galway University Hospital, a tertiary breast cancer referral centre serving the west of Ireland. All patients had a minimum follow-up of 5 years. Outcomes assessed included the development of wound complications and breast cancer recurrence. The data were evaluated by univariable and multivariable Cox regression analysis. Results: A total of 229 patients who underwent immediate reconstruction were identified. The overall 5-year recurrence-free survival rate was 85·6 per cent. Fifty-three patients (23·1 per cent) had wound complications, of whom 44 (19·2 per cent) developed a wound infection. There was a significantly greater risk of developing systemic recurrence among patients who experienced a postoperative wound complication compared with those without a complication (hazard ratio 4·94, 95 per cent c.i. 2·72 to 8·95; P < 0·001). This remained significant after adjusting for Nottingham Prognostic Index group in the multivariable analysis. The 5-year recurrence-free survival rate for patients who had a wound complication was 64 per cent, compared with 89·2 per cent in patients without a complication ( P < 0·001). Conclusion: This study has demonstrated that wound complications after immediate breast reconstructive surgery have significant implications for patients with breast cancer. Strategies are required to minimize the risk of postoperative wound complications in patients with breast cancer undergoing immediate reconstruction. Abstract : Preventive methods needed